The concept of validity in sociodental indicators and oral health-related quality-of-life measures - Brondani MA, MacEntee MI. (Blackwell Synergy, 2007)
Most of the psychometric instruments used to measure quality of life associated with oral impairment and disability from the perspectives of older adults focus on negative experiences, and pay little attention to the possibility of positive reactions to disablement